The concept of the covenant in establishing and maintaining the meaning and value of the church - Rabali, Thiofhitshithu (North-West University, 2004)
'Covenant' is one of the dominant themes in the Bible. The covenant theme can serve as a concept to understand and synthesize biblical revelation. The covenant theme is important and significant because it helps explain God's dealings with mankind, and help describe His relation with His people. In understanding what the covenant them entails helps in gaining deeper insight as to the nature and function of the church, as God's people and covenant community. There are various covenants in Scripture, and they are manifested in various forms. There are covenants made by people with each other, covenants made by people with God, and covenants made by God with people (divine covenants). The different and successive divine covenants (Noahic, Abrahamic, Davidic and the New covenant), each have their own uniqueness, but they also manifest great unity and complementarity. With each divine covenant, there is an element of freshness, but they harmonize as part of God's revelation and interaction with His people. God initiates the relationship and formalizes it with His people in covenantal form. The people become God's people and nation, who are subject to His rule, expressing loyalty and worshipping Him. The people (nation) become covenant partners with God, in carrying out His will and purpose. Then, the covenant then helps in understandig that the church is God's possession. God started the church, by redeeming for Himself people who will serve Him. One also understands that the church in the New Testament era is connected and related with God's people in the Old Testament period. This is so because of God's salvation plan fulfilled and carried out through Jesus. Jesus is the founder and shepherd of the church. The unity of the church with the Father and Christ is made possible by the working of the Holy Spirit. The church as covenant community reveals unity and fellowship, which exists because of their relation to God. The covenant community also exhibits aspects of being invisible and visible, of being an organism and an organization, and being exclusive and inclusive. The understanding of the covenant theme makes it clear that the church is of great value and worth in God's scheme, in accomplishing His will on earth. The church is significant and of high merit because of the grace of God invested in its existence and nature. The church is necessary for believers, and in the society as a whole. The importance and function of the church is manifested through the marks of a true church i.e. preaching the Word, administering of sacraments and exercising of discipline.
Thesis (M.Th. (Dogmatics))--North-West University, Potchefstroom Campus, 2005.